Citizen journalists and new media technology in the ASEAN region - Katz, James E. (2010)
This paper discusses citizen journalism and related volunteer news co-creation activities in Southeast Asia in order to understand their implications. These implications include, in rising order of abstractness, the operations of news organizations, the ability of governments to influence domestic and international perspectives, the information resources of citizens, and the formulation of public policy. The paper reviews a small number of case studies of citizen journalism activities from across the ASEAN region. The paper then suggests possible reasons why some endeavors were successful and others not. The paper next analyzes the relationship between citizen journalism activities and issues that are critical to the future of the region: freedom of information, human rights, self-determination, certification of professional journalists, democratic participation, security, and cultural harmony. The paper concludes by exploring likely future prospects for citizen journalism as region?s social conditions and technological infrastructure rapidly change.